Problems and reasons for the distance of correctional institutions About joining the right programs: (Analytical study) - Hadi, Amer Ali; Al-Alwani, Ammar Saleem (Al-Adab Journal, 2022)
With the development and change of societies, the problems increased and became complicated in a way that led to the need to organize social services, under the supervision of private authorities, to help the needy and achieve the goals of social development. Poor provision of rehabilitation programs or due to the large number of inmates inside the correctional institutions, as well as their personal problems. Therefore, some correctional institutions often tried to identify the problems that inmates suffer according to their own rehabilitation and correctional programs. Which constitutes an obstacle to improving the behavior of inmates due to these and other reasons.